2006
DOI: 10.1007/s00134-006-0344-x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of injury influences quality of life in survivors of acute respiratory distress syndrome

Abstract: QOL in survivors of ARDS appears to be influenced by the mechanism of lung injury (primary vs. secondary), lending support to the concept that ARDS is a heterogeneous condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 19 publications
1
9
1
Order By: Relevance
“…No differences in HRQL caused by respiratory distress were observed, in keeping with the results of Kim et al [15] Nonetheless, Parker et al, [32] who studied a larger number of patients over a longer follow-up period, reported more favorable recovery of HRQL in patients with ARDS of intrapulmonary origin. Similar to previous data reported, [25] , [33] no differences were found in HRQL according to whether patients lay in the prone position or whether they received inhaled nitric oxide or steroids.…”
Section: Discussionsupporting
confidence: 84%
“…No differences in HRQL caused by respiratory distress were observed, in keeping with the results of Kim et al [15] Nonetheless, Parker et al, [32] who studied a larger number of patients over a longer follow-up period, reported more favorable recovery of HRQL in patients with ARDS of intrapulmonary origin. Similar to previous data reported, [25] , [33] no differences were found in HRQL according to whether patients lay in the prone position or whether they received inhaled nitric oxide or steroids.…”
Section: Discussionsupporting
confidence: 84%
“…followed 73 patients with ARDS for 1 year after critical illness to specifically assess whether the underlying cause of ARDS affected quality of life scores. In fact, this group showed that patients with indirect ARDS had worse quality of life on the majority of domains tested, even when adjusted for duration of illness and comorbidities 47 .…”
Section: Clinical Differences Between Direct and Indirect Ardsmentioning
confidence: 89%
“…Aside from mortality, there have now been several studies that have measured indicators of quality of life after critical illness 4751 . Patients with ARDS have worse quality of life scores than patients without ARDS during critical illness and these impairments persisted over several years 48, 49, 51 .…”
Section: Clinical Differences Between Direct and Indirect Ardsmentioning
confidence: 99%
“…Angus et al [18] measured qualityadjusted survival in the first year only in pulmonary ARDS patients, and observed that the quality of life in those who survived was markedly impaired. Recently, Parker et al [19] found that the quality of life was similar in pulmonary and extrapulmonary ARDS patients at 3 months, but by 12 months patients with pulmonary ARDS had significantly better quality of life.…”
Section: Epidemiologymentioning
confidence: 97%